SINKRONISASI KOMPILASI HUKUM ISLAM DAN PERATURAN PERUNDANG-UNDANG INDONESIA - Andi Muhammad Syukur; Kurniati; Qadir Gassing (Nirta Learning Centre, 2025)
The research method in this study is a library method using a sociological approach and a normative approach. The results of this study are that the Compilation of Islamic Law in Indonesia is an effort to codify and compile legal regulations relating to Islamic family law, which include matters such as marriage, divorce, inheritance, and inheritance. KHI is very important because the Indonesian legal system generally recognizes legal plurality. The position of the Compilation of Islamic Law in the Indonesian Legislation System has a crucial role because it has a significant influence, especially in terms of the application of Islamic law in Indonesia. Harmonization of the Compilation of Islamic Law (KHI) with Indonesian Legislation is very important to create a fair legal system, which is not only in accordance with the principles of Islamic law, but also in line with the principles of the rule of law.